Something to See, Do, and Buy: Integrating Safety, Animal Welfare, and Visitor Experience in Conservation Tourism at Buaya Asam Kumbang - Yuliana Ristantya Ningsih; Sakira Putri Manurung; Sendi Permana; Nanda Oktarina Aditya; Tiara Ramadhanti Puspo; Hilda Syahrani; Yetti Anita Sari (Sustainability: Theory, Practice and Policy, 2026)
The sustainability of conservation tourism depends equally on wildlife preservation and the quality of the visitor experience. However, the integration of visitor safety, animal welfare, and interactive learning remains underexplored in destination management. This study investigates visitors’ perceptions of facilities, safety, and educational value at the Buaya Asam Kumbang Sanctuary, Medan, and analyzes their impact on the overall tourism experience. Employing a qualitative descriptive design, data were collected from September 2024 to January 2025 through semi-structured interviews, field observations, and documentation involving 30 informants. Data saturation and methodological triangulation were applied for analysis. Findings reveal that visitor perceptions align with the “something to see, do, and buy” framework but extend it significantly. Physical infrastructure and safety primarily shape initial impressions. Interactive activities, such as crocodile feeding, offer high educational value, yet this is strictly contingent upon visible staff supervision. Notably, visitors evaluate safety and animal welfare not as separate domains, but as a singular, integrated indicator of management quality. Furthermore, the lack of age-differentiated ticket pricing and limited food outlets were identified as critical unmet needs. Theoretically, this study expands the conventional attraction framework by embedding ethical and risk dimensions. Practically, it recommends implementing age-based ticketing, expanding culinary services, and formalizing transparent supervision protocols to enhance visitor satisfaction and destination sustainability.